City Development Strategy for Halong - National Institute for Urban and Rural Planning (World Bank, Hanoi, 2017)
By the year 2020, Ha Long will be a city of tourism, a center of seaborne commerce, a commercial capital and playing the role of a core urban area in the Northern region of Vietnam. It will be a place that will attract investment and tourism from all over the world with a growing, dynamic, stable economy which is environmentally friendly. Ha Long city will become an urban development co-existing harmoniously with the Ha Long Bay World Heritage Site. It will be a technological showpiece, equipped with the latest technical and social infrastructure meeting international standards It will be an eco-urban example of how to exist within a special heritage and culture and will ensure a high standard of living for all of its residents.